Positive Representations of Asexuality in Contemporary Young Adult - Simelane, Smangaliso (WritingThreeSixty, 2018)
According to Stacy Pinto, asexuality is one of the most underresearched, misunderstood, under-represented sexual identities of the 21st century (331) despite the fact that there currently exists ―a small social movement, perhaps akin to the gay rights movement of the 1960s and 1970s, which has brought together a diverse group of people who identify as asexual‖ (Bogaert 244). Due to the limited awareness of asexuality, relatively few asexual characters exist in literature and even fewer could be considered examples of positive representation. Instead, asexual representations in media tend to serve as ―denial narratives‖ (Przybylo 189) which invalidate the asexual identity and render asexuality illegible. The absence of positive asexual characters can have an alienating effect on those who identify as asexual and find themselves in a culture which promotes sexuality as a necessary part of human existence. A rise in fantasy novels that feature asexual protagonists may challenge the trend of asexual erasure and problematize prevailing notions of human sexuality. In the following thesis I investigate how the fantasy genre can facilitate the awareness and normalisation of asexual identities. This will be done by introducing and contextualising asexuality before discussing the effects of past negative representations of asexual characters in literature and popular media. Following this, I analyse two contemporary young adult fantasy novels, namely Clariel by Garth Nyx and Quicksilver by RJ Anderson, that feature positively portrayed asexual characters to determine how the fantasy elements and concepts such as identification with the protagonist (Varsam 205) effectively depathologizes queerness.